2021
DOI: 10.3390/ijerph18073500
|View full text |Cite
|
Sign up to set email alerts
|

Quadratus Lumborum and Transversus Abdominis Plane Blocks and Their Impact on Acute and Chronic Pain in Patients after Cesarean Section: A Randomized Controlled Study

Abstract: Background: Severe postoperative pain is a significant problem after cesarean sections. Methods: This study was a randomized, controlled trial of 105 patients conducted in two hospitals. All patients were anesthetized spinally for elective cesarean section. Each participant was randomly allocated to one of three study groups: the quadratus lumborum block (QLB) group, the transversus abdominis plane block (TAPB) group, or the control (CON) group. The primary outcome of this study determined acute pain intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
(7 reference statements)
1
16
0
Order By: Relevance
“… 86 , 88 , 89 A recently published study revealed that QLB not only reduced acute pain scores (with similar efficacy to TAPB during the acute phase) but also reduced the severity of persistent postoperative pain months after CS (with better efficacy than TAPB during the chronic phase). 90 More RCTs are needed to confirm these findings. The durations of other local anesthetic techniques were similar.…”
Section: Discussionmentioning
confidence: 99%
“… 86 , 88 , 89 A recently published study revealed that QLB not only reduced acute pain scores (with similar efficacy to TAPB during the acute phase) but also reduced the severity of persistent postoperative pain months after CS (with better efficacy than TAPB during the chronic phase). 90 More RCTs are needed to confirm these findings. The durations of other local anesthetic techniques were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several new approaches of QLB have been described, but the exact mechanism of the analgesic effect of quadratus lumborum block remains under anatomical, radiological, and neurophysiological investigation [20]. The main focus of most studies assessing the effectiveness of QLB and intrathecal morphine (ITM) is opioid consumption, time to first analgesia, and pain severity in standardized pain scores (NRS, VAS, or NPSI-Neuropathic Pain Symptom Inventory) [1][2][3][4]21]. These studies indicate that most effective method in postoperative pain control after cesarean section remains the administration of ITM also when compared with QLB.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of CPSP is still under debate and no targeted treatment is available at this time [30]. Although the occurrence of CPSP following cesarean section is lower than for other types of surgery [2], the constant increase in the number of cesarean sections globally makes CPSP a possible growing problem [31]. To date, few studies have been published assessing the possible effect of regional anesthesia on the occurrence of CPSP in patients after cesarean section [2,9,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quadratus lumborum block (QLB) is a relatively new regional anesthesia technique; it was developed by Blanco [7] and has been proposed as an analgesic alternative for use after many types of surgical procedures [8][9][10]. Several approaches to QLB have been reported [11], but only a few randomized controlled trials (RCT) [4,5,12,13] have evaluated the use of QLB for nephrectomies, all of which concerned laparoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%